High-Aspect-Ratio TiO2 Nanotube Layers via Galvanostatic Anodization in an Electrolyte Containing Lactic Acid - Alijani, Mahnaz; Sopha, Hanna; Ng, Siowwoon; Rodriguez-Pereira, Jhonatan; Macak, Jan M. (Physica Status Solidi-Rapid Research Letters, 2021)
1D TiO2 nanotubes (TNTs) produced by anodization of Ti have attracted significant research and technological interest due to their excellent properties suitable for numerous applications. A huge challenge that remains is to develop reproducible protocols for the synthesis of extremely high aspect ratio (HAR) TNT layers. A new strategy for the growth of HAR TNT layers based on galvanostatic anodization of Ti in NH4F/ethylene-glycol-based electrolyte with the addition of lactic acid (LA) is described. The results show that the addition of LA to the electrolyte can effectively prevent the dielectric breakdown during the anodization at elevated current densities. In comparison with the LA-free electrolyte, robust HAR TNT layers as thick as ≈44 μm can be produced within 15 min.
CRIS-Team Scopus Importer:2022-11-02
Keywords: anodization; breakdown; galvanostatic method; lactic acid; TiO